Transcriptomic and Metabolomic Analyses Provide Insights Into an Aberrant Tissue of Tea Plant (Camellia sinensis) - Liu, Ding-Ding; Wang, Jun-Ya; Tang, Rong-Jin; Chen, Jie-Dan; Liu, Zhen; Chen, Liang; Yao, Ming-Zhe; Ma, Chun-Lei (Frontiers in Plant Science, 2021)
Tea plant (Camellia sinensis (L.) O. Kuntze) is one of the most important economic crops with multiple mutants. Recently, we found a special tea germplasm that has an aberrant tissue on its branches. To figure out whether this aberrant tissue is associated with floral bud (FB) or dormant bud (DB), we performed tissue section, transcriptome sequencing and metabolomic analysis of these tissues. Longitudinal sections indicated the aberrant tissue internal structure was more like a special bud (SB), but was similar to that of DB. Transcriptome data analysis showed that the number of heterozygous and homozygous SNPs was significantly different in the aberrant tissue compared with FB and DB. Further, by aligning the unmapped sequences of the aberrant tissue to the Non-Redundant Protein Sequences (NR) database, we observed that 36.13% of unmapped sequences were insect sequences, which suggested that the aberrant tissue might be a variation of dormant bud tissue influenced by the interaction of tea plants and insects or pathogens. Metabolomic analysis showed that the differentially expressed metabolites (DEMs) between the aberrant tissue and DB were significantly enriched in the metabolic pathways of biosynthesis of plant hormones and biosynthesis of phenylpropanoids. Subsequently, we analyzed the differentially expressed genes (DEGs) in the above mentioned two tissues, and the results indicated that photosynthetic capacity in the aberrant tissue was reduced, whereas the ethylene, salicylic acid and jasmonic acid signaling pathways were activated. We speculated that exogenous infection induced programmed cell death (PCD) and increased the lignin content in dormant buds of tea plants, leading to the formation of this aberrant tissue. This study advanced our understanding of the interaction between plants and insects or pathogens, providing important clues about biotic stress factors and key genes that lead to mutations and formation of the aberrant tissue.